1708. Impacts of age and season on rates of hospitalization for respiratory syncytial virus (RSV) in infants in the United States and their use of mechanical ventilation and charges. (31st December 2020) - Shepard, Donald S
Abstract: Background: Respiratory Syncytial Virus (RSV) infection is the leading cause of hospitalization in infants below age 12 months and highest below age 6 months. Despite considerable evidence on the clinical predictors of RSV hospitalizations, little is known about their cost, its drivers and their relation to age and season. Methods: We used the National Inpatient Sample to examine RSV inpatient admissions and their average charge from 2009 to 2011. This 3-year data set includes a large, nationally representative all-payer sample of 37, 376 RSV admissions of infants in the US under age 12 months recorded by month. We calculated the rate per 1000 infants of RSV hospitalizations, the share receiving mechanical ventilation (MV), and the mean charge per admission (separated by use of MV) with 95% confidence intervals by age and season, excluding incomplete data. We adjusted charges to Jan 2020 based on the medical care Consumer Price Index. Results: These data confirm that rates of hospitalization by age were highest for infants 1 month of chronological age (2.42 times the annualized average) and declined steadily thereafter. The percentage of hospitalizations with MV declined from months < 1 to 4, with subsequent fluctuations (Fig 1). Charges exceeded the annual average only for infants aged < 1 and 1 month (Fig 2). In 2020 prices, hospitalization charges per episode averaged 175, 211 with MV vs. 17, 313 without MV, totaling 1.51 billion annually for the birth cohort of 4.04 million infants (374 per infant). As only 4.5% of hospitalizations had MV, those without MV comprised 67.5% of aggregate yearly charges. Admissions were highly seasonal, with the rate in the highest month (Feb) 341 times that in the lowest month (July). However, utilization of MV (Fig 3) tended to be lower in the RSV season but depended mostly on age. While average charges were higher outside the RSV season, their seasonal pattern was similar for admissions with and without MV. Fig. 1. Share of hospitalizations with RV (bars) vs. rate of RSV hospitalizations (line) by age Fig. 2. Charges (bars) vs. rate of RSV hospitalizations (line) by age Fig. 3. Utilization of MV (bars) vs RSV hospitalization rate (line) by season Conclusion: RSV in infants under one year generate substantial hospital charges. While each of the small share of infants receiving MV is expensive, infants with MV are not the main driver of costs (Fig 4). Rather, the large number and share (94.5%) of hospitalizations without MV is the major determinant of aggregate charges (Fig 5). Fig. 4. Relation between use of mechanical ventilation (MV) [bars] and RSV hospitalization rate [lines] by season and age (in months) Fig. 5. Hospitalization charges (bars) vs RSV hospitalization rate (line) by season Disclosures: Donald S. Shepard, PhD, Sanofi Pasteur (Grant/Research Support)